Availability Of Fish Fauna In Some Selected Districts In Bangladesh - Chandra, KJ (Bangladesh Journal of Animal Science, 2012)
A check-list of 139 species of fishes of both exotic and indigenous origin belonging to 34 families and 87 genera available in the rivers, beels, haors, ponds and swamps of the greater Mymensingh (Mymensingh, Kishoregonj, Netrakona, Jamalpur and Sherpur) districts of Bangladesh is presented. The number of species, genera and family of fishes reported in Mymensingh regions is still rich in fresh water fish fauna. The systematic, ecology, Distribution, habits of these fish fauna of greater Mymensingh region need to be studied. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9924 BJAS 2009; 38(1-2): 151-163